Research on physical and mechanical properties of fabrik selected for special clothing of preschool children - Juraeva, Madina; Nabidjonova, Nargiza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article discusses the research on physical and mechanical properties of fabrics and clothing proposed for preschool children to prevent contamination. The purpose of poposing special clothing is to consider the health and comfort of young childeren.